Growth and productivity of maize (Zea mays L.) under precision nutrient management - Shyam C.S.; S.S. Rathore; Kapila Shekhawat; R.K. Singh; V.K. Singh (Annals of Agricultural Research, 2022)
A field experiment on precision nutrient management in maize was conducted at experimental research farm of ICAR-Indian Agricultural Research Institute, New Delhi, India during kharif 2018, with the objective to enhance the growth and productivity of maize. The treatments included nutrient management through Nutrient Expert® and Green Seeker®in comparison with state recommendation. The growth (plant height, dry matter and leaf area) and yield attributes (cob length and cob girth) were recorded higher under precision nutrient management practices of NE + GS7T, NE6T, NE7T and NE + GS 6T. The maximum leaf area (3959 cm2 ) at 90 DAS was recorded with NE7T. Maximum cob length recorded was 15.92 cm under NE7T. Grain (6.2 t/ha) and cob yield (7.9 t/ha) of maize was also recorded highest under NE7T nutrient management. Hence, fertilizer management in maize crop based on Nutrient Expert® with yield target of 7t/ha under Trans-Gangetic plain (TGP) was found promising.